Design of Plasmonic Yagi–Uda Nanoantennas for Chip-Scale Optical Wireless Communications - Gabriel H. B. Damasceno; William O. F. Carvalho; Jorge Ricardo Mejía-Salazar (Sensors, 2022)
Optical wireless transmission has recently become a major cutting-edge alternative for on-chip/inter-chip communications with higher transmission speeds and improved power efficiency. Plasmonic nanoantennas, the building blocks of this new nanoscale communication paradigm, require precise design to have directional radiation and improved communication ranges. Particular interest has been paid to plasmonic Yagi–Uda, i.e., the optical analog of the conventional Radio Frequency (RF) Yagi–Uda design, which may allow directional radiation of plasmonic fields. However, in contrast to the RF model, an overall design strategy for the directional and optimized front-to-back ratio of the radiated far-field patterns is lacking. In this work, a guide for the optimized design of Yagi–Uda plasmonic nanoantennas is shown. In particular, five different design conditions are used to study the effects of sizes and spacing between the constituent parts (made of Au). Importantly, it is numerically demonstrated (using the scattered fields) that closely spaced nanoantenna elements are not appropriated for directional light-to-plasmon conversion/radiation. In contrast, if the elements of the nanoantenna are widely spaced, the structure behaves like a one-dimensional array of nanodipoles, producing a funnel-like radiation pattern (not suitable for on-chip wireless optical transmission). Therefore, based on the results here, it can be concluded that the constituent metallic rib lengths must be optimized to exhibit the resonance at the working wavelength, whilst their separations should follow the relation <semantics>λeff/π</semantics>, where <semantics>λeff</semantics> indicates the effective wavelength scaling for plasmonic nanostructures.